Biosintesis ZnO Nanopartikel dari Ekstrak Air Daun Jambu Biji (Psidium guajava L) dan Ion Zn2+ serta Interaksinya dengan Kitosan sebagai Antibakteri Escherichia coli - Ahmad Fatoni; Hilma Hilma; Ade Arinia Rasyad; Selly Novriyanti; Nurlisa Hidayati (Fakultas Farmasi Universitas Andalas, 2020)
The biosynthesis of ZnO nanoparticles and chitosan-ZnO nanoparticles has been carried out. The aims of this research were to modify and characterize of chitosan-ZnO nanoparticles and their application as an antibacterial agent of Escherichia coli. The characterization of chitosan-ZnO nanoparticles was conducted by FTIR spectroscopy and X-Ray diffractometer. ZnO nanoparticle was synthesized by the reaction between leaf extract of the common guava (Psidium guajava L) and zinc acetate dihydrate. Chitosan-ZnO nanoparticles were synthesized by the reaction between chitosan and ZnO nanoparticles. The agar diffusion method was used to study the antibacterial activity of chitosan-ZnO nanoparticles. The result showed that the wavenumber of FTIR spectra chitosan-ZnO nanoparticles appeared at 3427 cm−1. The crystalline size of ZnO nanoparticles was 16.54 nm. The average inhibition zone of chitosan-ZnO nanoparticles at concentration 10,000; 5,000; and 2.500 mg/L were 30.57 ± 0.87; 25.97 ± 1.42; and 23.10 ± 1.61 mm, respectively. The higher the concentration of chitosan-ZnO nanoparticles, the greater the inhibition zone.